A Brief Review on Nutraceuticals and its Application - Jain, Sameeksha; Purohit, Arpana; Nema, Prakhar; Vishwakarma, Harshna; Jain, Prateek Kumar (Asian Journal of Dental and Health Sciences, 2022)
Because of their putative safety, nutraceuticals have sparked tremendous interest. Nutraceuticals are nutritional supplements that are used to improve health, postpone aging, prevent disease and support the healthy functioning of the human body. Nutraceuticals are currently gaining popularity due to their nutritional and medicinal properties. They are classified as dietary supplements or herbal bioactive substances based on their source. Herbal nutraceuticals aid in the maintenance of health and the promotion of optimal health, longevity, and quality of life. Nutraceuticals have demonstrated encouraging results in the treatment of a variety of ailments, including cancer, neurological diseases, cardiovascular disease, and others. The current review provides an overview of several bioactive substances that operate as nutraceuticals (carbohydrates, lipids, edible flowers, alkaloids, medicinal plants, etc.) and their involvement in health benefits. Focus on the need for appropriate diets, health issues associated with failure to adhere to known healthy eating models, development of new nutraceuticals/functional foods/food supplements with novel health benefits, elucidation of mechanisms of action of these products, and to define and understand the analytical, formulation, and regulatory aspects of nutraceuticals. The use of nutraceuticals in the prevention of certain diseases has also been addressed. Keywords: Nutraceutical, Dietary supplements, Herbal bioactive compounds, Application